Biological perspectives on Hittite brewing - Brown, Michael (Journal of archaeological science reports, 2018)
This study examines biological properties of beer in ancient Anatolia. Discussion focuses on the Hittite site of Kuşaklı-Sarissa, where the remains of a brewery were excavated dating to the second millennium BC. While ancient brewing practices have often been investigated using archaeological and textual sources, relatively little scholarship has addressed the chemical constituents of this process. The following review makes use of a wider body of food science and medical literature in order to shed light on the sensory and nutritional characteristics of alcoholic beverages.